Implementasi Model Problem Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Zaidah, Alpi; Hidayatulloh, Alpiana (LPPM Institut Pendidikan Nusantara Global, 2024)
Research action This aim for increase ability think critical student with using the Problem Based Learning model in the Physics course Basic I material mechanics fluid, with subject study student Science Education Institute Global Archipelago Education in the first semester of the 2023 /2024 academic year. Classroom Action Research This consists from four stages, namely planning, implementation, observation and reflection. Technique data collection with observations, test, notes field and documentation. Meanwhile the data is analyzed with use technique qualitative descriptive. Results study show that use of the Problem Based Learning model can increase ability think critical student on material mechanics fluid. Enhancement ability think critical student be marked with enhancement percentage average aspect value ability think critical ie with percentage average value 60.91% on stage pre-action to 71.96% after action cycle 1 with criteria Enough Good And return increase after done action cycle 2 with percentage average value 86.25% with criteria Good. From these data it can be seen that implementation Problem Based Learning model can increase ability think critical student.